Epitaxy of Radial High‐Energy‐Facetted Ultrathin TiO2 Nanosheets onto Nanowires for Enhanced Photoreactivities. (28th January 2016) - Lin, Haifeng; Wang, Xun
Abstract : Rational design and construction of novel nanostructures with outstanding functions, and investigation on the relationship between their structures and properties have continuously been intriguing but are still challenging now. In this work, 1D TiO2 (B) hierarchitectures with epitaxial 100 and 010 high‐energy‐facetted ultrathin 2D nanosheets that are parallel to the c ‐axis are demonstrated for the first time. These hierarchitectures show much improved photochemical properties as compared with the nanoparticles and nanowires as well as the physical mixture of nanosheets and nanowires. These include photodegradation of methyl orange and water splitting, due to the remarkably increased surface area and active sites, and enhanced separation and transport of charge carriers. The findings reported here may inspire the engineering of highly active nanostructures for energy and environment related applications. Abstract : 1D TiO2 hierarchitectures with epitaxial 100 and 010 high‐energy‐facetted ultrathin nanosheets have been constructed for the first time. The hierarchitectures exhibit superior characteristics compared to nanoparticles, nanowires, and the physical mixture of nanosheets and nanowires: surface area, number of active sites, and separation of electron–hole pairs are significantly increased. In consequence, the photocatalytic performance is much superior.